The immune system - Edelson, Edward, 1932- (New York : Chelsea House, 1989)
Examines the workings of a complex structure, the body's defense against disease and infection.
Includes index.
Bibliography: p. 96-97.
Booklist.
Wilson's Junior High School.
Wilson's Senior High School.
8.9
Keywords: Immune system -- Juvenile literature; Immune system; Immunology